Synthesis and biological activities of alcohol extract of black cumin seeds (Bunium persicum)-based gold nanoparticles and their catalytic applications - Bahattab Omar (De Gruyter, 2021)
Fast, simple, and environmentally friendly gold nanoparticles (Au-NPs) capped and stabilized with black cumin (Bunium persicum) seed alcohol extract are reported. The aqueous gold ions (Au3+) were treated with B. persicum (BP) seed extract, which resulted in a rapid color change to red, indicating the synthesis of Au-NPs. UV-Vis spectroscopy, FTIR, SEM, energy dispersive X-ray (EDX), and X-ray diffraction (XRD) techniques were used to further characterize the Au-NPs. Its stability was assessed against various pH levels and sodium chloride levels (NaCl), different salts of same concentration as well as at a range of temperature (30–100°C). The UV-Vis spectrum in the Au-NPs produced a 540 nm plasmon surface resonance, and a 25–50 nm range of particulates was shown in the SEM analysis. In addition, the FTIR spectra confirmed the inclusion in the capping and decrease of Au-NPs of amines, amide groups, and alcohols. The EDX analysis confirmed the presence of element Au. Furthermore, Au-NPs were tested for enzyme inhibition and antibacterial and antifungal activities and showed remarkable response. These findings have concluded that BP seed extract is an effective bio-reductant of gold nanoparticle synthesis, which can be further applied in different biomedical and pharmaceutical industries.